One-step solvothermal synthesis of hierarchically porous nanostructured CdS/TiO heterojunction with higher visible light photocatalytic activity - Yang, G; Yang, B; Xiao, T; Yan, Z (2013)
One-step solvothermal method was developed for the synthesis of hierarchically porous nanostructured CdS/TiO heterojunction materials, which exhibited enhanced visible-light-driven photocatalytic activity in decomposing both methyl orange (MO) and rhodamine B (RhB) in water. The photocatalyst with the highest performance was the one prepared using the Ti:Cd molar ratio of 1:1. Based on the characterization results of XRD, XPS, FT-IR, SEM, HRTEM, UV-vis DRS and N adsorption-desorption, the influence of coupling TiO with CdS on the crystal phase, band structure, surface element composition, morphology, optical absorption and surface area of the as-prepared samples are investigated. The results showed that the CdS/TiO heterojunction catalysts possessed well-defined hierarchically porous structure composed of anatase TiO and hexagonal CdS nanoparticle with average grain size of 4-6 nm. Their enhanced catalytic activity can be attributed to the synergistic effect of crystal compositions, porous architectures, electronic band structure, large specific surface area and strong visible light absorption. © 2013 Elsevier B.V. All rights reserved.